Anharmonic EXAFS and its Parameters of HCP Crystals: Theory and Comparison to Experiment - Hung, Nguyen Van; Viet, Dao Xuan (Communications in Physics, 2007)
A new theory for ab initio calculation of the anharmonic Extended X-ray Absorption Fine Structure (EXAFS) and its parameters of hcp crystals has been developed based on the single- shell model. Analytical expressions for the anharmonic contributions to the amplitude and to the phase of EXAFS and a new anharmonic factor have been derived. The EXAFS cumulant expressions are formulated based on the anharmonic correlated Einstein model. The EXAFS function and its parameters contain anharmonic effects at high temperature and appoach those of the harmonic model at low temperature. Numerical results for Zn agree well with the experimental values